TINJAUAN PENGARUH DIAMETER BUTIRAN TANAH TERHADAP NILAI KOHESI, C DAN SUDUT GESER DALAM, ïª - Afriani, Lusmeilia (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Research about the influence of soil grain size to the value of cohesion c and internal shear angle j has been done by using direct shear test apparatus. The size of this instrument is a large box 500 x 500 x 300 mm. The soil sample for this research took from Criquebeuf-sur-Seine, Seine Maritime, North French. The soil grain size are 0/25 mm, 0/50 mm and 0/80 mm and it is classified as the coarse sol type. These results were then compared with that it uses sand sample from Fountainebleau, France. This research was done in the Regional Laboratorium of Street and Bridge in Rouen. Until now, research in the coarse grain soil are very rare due to the lack of instrument and facilities. The result indicates an important things where the grain size of soil will influences the cohesion value c, and the internal shear angle j. These values can be obtained from Mohr-Coulomb curve.